2008
DOI: 10.1021/jp0774589
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalysts with Tunable Properties Derived from Polystyrene-b-poly(vinyl pyridine) Block Copolymer Templates for Achieving Controllable Carbon Nanotube Synthesis

Abstract: Chemical vapor deposition, one of major carbon nanotube synthesis techniques, has demonstrated great promise for substrate-based carbon nanotube device applications. To understand carbon nanotube growth mechanisms for achieving controllable synthesis, thereby producing carbon nanotubes with consistent and predefined behavior for materializing their highly touted properties, it is imperative to develop a methodology to create nanocatalyst systems controllably with great tunability. In this paper, a comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Self‐assembled block copolymers have been widely employed to create periodically ordered nanoparticle arrays on various substrates. Iron, cobalt, nickel and gold nanoparticles prepared with the block copolymers have been successfully used for the synthesis of SWCNTs 7–10, 13, 16, 17. It has been demonstrated that metal nanoparticle arrays with adjustable spacing, size and composition can be prepared using a solution micelle template formed by polystyrene‐ b ‐poly(vinylpyridine).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Self‐assembled block copolymers have been widely employed to create periodically ordered nanoparticle arrays on various substrates. Iron, cobalt, nickel and gold nanoparticles prepared with the block copolymers have been successfully used for the synthesis of SWCNTs 7–10, 13, 16, 17. It has been demonstrated that metal nanoparticle arrays with adjustable spacing, size and composition can be prepared using a solution micelle template formed by polystyrene‐ b ‐poly(vinylpyridine).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that metal nanoparticle arrays with adjustable spacing, size and composition can be prepared using a solution micelle template formed by polystyrene‐ b ‐poly(vinylpyridine). These nanoparticles are excellent catalysts enabling the growth of high‐quality and low‐defect SWCNTs 8–10, 16, 17…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With PS-b-P4VP, NP inclusion can be done either by depositing the NPs aer the self-assembly process or inclusion of the desired ratio of NP to the diblock copolymer solution before spin coating. For example, wellordered micelle and cylindrical microdomains have been reported in PS-b-P4VP BCPs for metal inclusion to fabricate arrays of iron nanocatalyts, 26 copper nanocatalyts, 27 titania NPs, 28 and iron platinum NPs.…”
Section: 22mentioning
confidence: 99%